Pregunta
upstudy study bank question image url

lolve each of the following quadritic equations by factorisation 7. \( (x+4)(x+6)=8 \) 1. \( (x-8)(x-4)=12 \) o. \( x^{2}-13 x+40=0 \) 2. \( x^{2}-49=0 \) 15 \( 4 x^{2}+4 x-3=0 \) 18. \( 2 x(x-3)+10=(x+1)(x+2) \) 17. \( x(x+1)=2 \) 19. \( (x+1)(x+2)+(x+3)(x+1)=x(x+1) \).

Ask by Fowler Moran. in South Africa
Feb 24,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Here are the solutions to the quadratic equations by factorization: 1. \( x = 10 \) or \( x = 2 \) 2. \( x = -2 \) or \( x = -8 \) 3. \( x = 5 \) or \( x = 8 \) 4. \( x = 7 \) or \( x = -7 \) 5. \( x = \frac{1}{2} \) or \( x = -\frac{3}{2} \) 6. \( x = 1 \) or \( x = 8 \) 7. \( x = -2 \) or \( x = 1 \) 8. \( x = -1 \) or \( x = -5 \)

Solución

Below are step‐by‐step solutions for each of the quadratic equations using factorisation. ───────────────────────────── 1. Solve (x – 8)(x – 4) = 12 • Expand the left side:   (x – 8)(x – 4) = x² – 4x – 8x + 32 = x² – 12x + 32 • Set the equation to zero by subtracting 12 from both sides:   x² – 12x + 32 – 12 = 0 ⟹ x² – 12x + 20 = 0 • Factor the quadratic. We look for two numbers that multiply to 20 and add to –12. These are –10 and –2:   x² – 12x + 20 = (x – 10)(x – 2) • Set each factor equal to zero:   x – 10 = 0 ⟹ x = 10   x – 2 = 0  ⟹ x = 2 ───────────────────────────── 2. Solve (x + 4)(x + 6) = 8 • Expand:   (x + 4)(x + 6) = x² + 6x + 4x + 24 = x² + 10x + 24 • Subtract 8 from both sides:   x² + 10x + 24 – 8 = 0 ⟹ x² + 10x + 16 = 0 • Factor the quadratic. Find two numbers that multiply to 16 and add to 10. They are 2 and 8:   x² + 10x + 16 = (x + 2)(x + 8) • Set each factor to zero:   x + 2 = 0 ⟹ x = –2   x + 8 = 0 ⟹ x = –8 ───────────────────────────── 3. Solve x² – 13x + 40 = 0 • Factor by looking for two numbers that multiply to 40 and add to 13. These are 5 and 8:   x² – 13x + 40 = (x – 5)(x – 8) • Set each factor equal to zero:   x – 5 = 0 ⟹ x = 5   x – 8 = 0 ⟹ x = 8 ───────────────────────────── 4. Solve x² – 49 = 0 • Recognize this as a difference of two squares:   x² – 49 = (x – 7)(x + 7) • Set each factor to zero:   x – 7 = 0 ⟹ x = 7   x + 7 = 0 ⟹ x = –7 ───────────────────────────── 5. Solve 4x² + 4x – 3 = 0 • Factor the quadratic. We look for factors in the form (ax + b)(cx + d) such that:   (2x – 1)(2x + 3) expands as:     2x · 2x = 4x²     2x · 3 + (–1) · 2x = 6x – 2x = 4x     (–1)(3) = –3   Thus, 4x² + 4x – 3 = (2x – 1)(2x + 3) • Set each factor to zero:   2x – 1 = 0 ⟹ 2x = 1 ⟹ x = ½   2x + 3 = 0 ⟹ 2x = –3 ⟹ x = –3/2 ───────────────────────────── 6. Solve 2x(x – 3) + 10 = (x + 1)(x + 2) • Expand both sides:   Left: 2x(x – 3) + 10 = 2x² – 6x + 10   Right: (x + 1)(x + 2) = x² + 3x + 2 • Bring all terms to one side:   2x² – 6x + 10 – (x² + 3x + 2) = 0   x² – 9x + 8 = 0 • Factor the quadratic. We need two numbers that multiply to 8 and add to –9. They are –1 and –8:   x² – 9x + 8 = (x – 1)(x – 8) • Set each factor equal to zero:   x – 1 = 0 ⟹ x = 1   x – 8 = 0 ⟹ x = 8 ───────────────────────────── 7. Solve x(x + 1) = 2 • Expand:   x² + x = 2 • Rearrange to bring everything to one side:   x² + x – 2 = 0 • Factor the quadratic. Find two numbers that multiply to –2 and add to 1. They are 2 and –1:   x² + x – 2 = (x + 2)(x – 1) • Set each factor to zero:   x + 2 = 0 ⟹ x = –2   x – 1 = 0 ⟹ x = 1 ───────────────────────────── 8. Solve (x + 1)(x + 2) + (x + 3)(x + 1) = x(x + 1) • Notice that (x + 1) is common in the left-hand terms. Factor it out:   (x + 1)[(x + 2) + (x + 3)] = (x + 1)(2x + 5) • The equation becomes:   (x + 1)(2x + 5) = x(x + 1) • Subtract x(x + 1) from both sides:   (x + 1)(2x + 5 – x) = 0   (x + 1)(x + 5) = 0 • Set each factor equal to zero:   x + 1 = 0 ⟹ x = –1   x + 5 = 0 ⟹ x = –5 ───────────────────────────── Summary of Answers: 1. (x – 8)(x – 4) = 12 ⟹ x = 10 or x = 2 2. (x + 4)(x + 6) = 8  ⟹ x = –2 or x = –8 3. x² – 13x + 40 = 0   ⟹ x = 5 or x = 8 4. x² – 49 = 0      ⟹ x = 7 or x = –7 5. 4x² + 4x – 3 = 0   ⟹ x = ½ or x = –3/2 6. 2x(x – 3) + 10 = (x + 1)(x + 2) ⟹ x = 1 or x = 8 7. x(x + 1) = 2     ⟹ x = –2 or x = 1 8. (x + 1)(x + 2) + (x + 3)(x + 1) = x(x + 1) ⟹ x = –1 or x = –5 These are the solutions to the given quadratic equations by factorisation.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

Let's take a look at how to solve these quadratic equations by factorization! The first equation, \( (x-8)(x-4)=12 \), can be rewritten as \( (x-8)(x-4) - 12 = 0 \). Expanding it gives us \( x^2 - 12x + 32 - 12 = 0 \), leading us to \( x^2 - 12x + 20 = 0 \). Factoring this yields \( (x-2)(x-10)=0 \), giving us solutions \( x = 2 \) and \( x = 10 \). For the equation \( x^2 - 49 = 0 \), this is a difference of squares! That's lovely. We can factor it as \( (x-7)(x+7) = 0 \), leading to the solutions \( x = 7 \) and \( x = -7 \). Remember when you see \( a^2 - b^2 \) it always factors into \( (a-b)(a+b) \)—a nifty little shortcut! Got it? Now go ahead and tackle those other equations with confidence!

preguntas relacionadas

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Álgebra Mexico Feb 26, 2025
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad